SuperSelective PCR primers for determining cis/trans configurations of mutations within the same gene - Diana Yaneth Vargas; Fred Russell Kramer (PLoS ONE, 2026)
In non-small cell lung cancer, the choice of an effective targeted therapy often depends on the presence of a somatic mutation that alters an amino acid in a key protein. However, if an additional somatic mutation occurs in the same mutant gene, causing an additional amino acid substitution to occur in that protein, the targeted therapy can become ineffective. A PCR assay has now been developed that utilizes two different SuperSelective primers, one primer for the amplification of the DNA strand containing the original somatic mutation, and a second primer for the amplification of the DNA strand containing the additional somatic mutation. Exponential amplification only occurs if these two somatic mutations occur in cis on the DNA molecule present in the same sister chromosome, and does not occur at all if the two different somatic mutations occur in trans on different DNA molecules in two different sister chromosomes. Significantly, if only one of these two mutations is present, amplification does not occur, thereby ensuring that the assay specifically detects the coexistence of both target mutations being present on the same DNA strand. This assay (demonstrated utilizing EGFR exon 20 mutations T790M and C797S) is extraordinarily sensitive, enabling the early substitution of a more effective therapy if the two mutations occur in a cis configuration. Moreover, these SuperSelective PCR assays can utilize DNA fragments isolated from noninvasive liquid biopsy samples, and they can be carried out on widely available spectrofluorometric thermal cyclers.